Comparison of hematologic, biochemical, and coagulation parameters in α1,3-galactosyltransferase gene-knockout pigs, wild-type pigs, and 4 primate species - Ekser, Burcin (2012)
BACKGROUND: The increasing availability of genetically-engineered pigs is steadily improving the results of pig organ and cell transplantation in nonhuman primates (NHPs). Current techniques offer knock-out of pig genes and/or knock-in of human genes. Knowledge of normal values of hematologic, biochemical, coagulation, and other parameters in healthy genetically-engineered pigs and NHPs is important, particularly following pig organ transplantation in NHPs. Furthermore, information on parameters in various NHP species may prove important in selecting the optimal NHP model for specific studies. METHODS: We have collected hematologic, biochemical, and coagulation data on 71 α1,3-galactosyltransferase gene-knockout (GTKO) pigs, 18 GTKO pigs additionally transgenic for human CD46 (GTKO.hCD46), 4 GTKO.hCD46 pigs additionally transgenic for human CD55 (GTKO.hCD46.hCD55), and 2 GTKO.hCD46 pigs additionally transgenic for human thrombomodulin (GTKO.hCD46.hTBM). RESULTS: We report these data and compare them with similar data from wild-type pigs, and the 3 major NHP species commonly used in biomedical research (baboons, cynomolgus, and rhesus monkeys) and humans, largely from previously published reports. CONCLUSIONS: Genetic modification of the pig (e.g., deletion of the Gal antigen and/or the addition of a human transgene) (i) does not result in abnormalities in hematologic, biochemical, or coagulation parameters that might impact animal welfare, (ii) seems not to alter metabolic function of vital organs, though this needs to be confirmed after their xenotransplantation, and (iii) possibly (though by no means certainly) modifies the hematologic, biochemical, and coagulation parameters closer to human values. The present study may provide a good reference for those working with genetically-engineered pigs in xenotransplantation research and eventually in clinical xenotransplantation.